A systematic review on the role of mitochondrial dysfunction/disorders in neurodevelopmental disorders and psychiatric/behavioral disorders - Pinto Payares, Daniela V.; Spooner, Logan; Vosters, Jennifer; Dominguez, Samantha; Patrick, Lauren; Harris, Ann; Kanungo, Shibani (Frontiers in Psychiatry, 2024)
Mitochondrial diseases are known inborn errors affecting energy metabolism and are as common as chronic diseases such as diabetes, affecting approximately 1 in 5,000 people. The role of mitochondrial diseases or mitochondrial dysfunction has been highlighted in neurodevelopmental disorders like ASD, ADHD, intellectual disability, and speech delay, as well as various psychiatric/behavioral disorders. Neurodevelopmental disorders are increasingly recognized as having behavioral and psychiatric symptoms. Our study aimed to investigate reports of mitochondrial disorders, noting neurodevelopmental disorders and psychiatric/behavioral disorders. This was done through a systematic review of literature from PubMed/MEDLINE, Scopus, and Cochrane Library up to November 2022. We found 277 publications, of which 139 met the inclusion criteria. We mostly found review articles with mention of mitochondrial dysfunction/disorder in relation to ASD with brief mentions of psychiatric/behavioral comorbidities. This suggests a need for broader research efforts beyond ASD to understand the relationship between mitochondrial dysfunction and various neurodevelopmental and psychiatric/behavioral comorbidities.